Approaches To Preparing Prospective College Teachers. I. Doctoral Programs with Emphasis Upon Preparing Graduate Students for College Teaching. II. The Doctorate of Arts Degree - Spalding, Willard; California State Coordinating Council for Higher Education, Sacramento ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This report discusses two possible approaches to maximize interest and aptitude in meeting the need for college instructors who are both scholars and teachers. Part I of the document concerns the extent to which existing graduate programs emphasize training for eventual college instruction. Part II addresses the possible development of doctoral level programs designed to emphasize classroom instruction rather than research in a given discipline. This portion of the report was prepared in particular response to a legislative resolution requesting such study. Based upon information presented in this report, the Council recommended (1) specific ways to expand and improve existent programs; (2) that no doctoral teaching program be initiated at this time; and (3) that the entire report be submitted to the legislature for information. Significant data are contained in tables and appendices. Part II has a seven page bibliography. (NF)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Instruction; Graduate Study; Professional Education; College Faculty; Doctoral Degrees; Doctoral Programs; Graduate Students; Higher Education; University of California